Postmodernistyczne metamorfozy baśni w Polsce - Szymborska, Karolina (Śląskie Studia Polonistyczne, 2018)
The author provides reflections upon the influence of postmodern literary tendencies on a fable. Contemporary metamorphoses of a fable are characterised by an attempt at deconstructing the genre, connected with various strategies of intertextual play with literary tradition (autoreflection, metaliterature, metatextuality, intertextuality, astiche, collage, parody etc.). This process is demonstrated on the example of the chosen postmodern fables written by Grzegorz Kasdepke, Marta Guśniowska, Agnieszka Suchowierska.